Appealing to Scripture in moral debate : five hermeneutical rules - Cosgrove, Charles H (Grand Rapids, Mich. : W.B. Eerdmans Pub., 2002)
Arguing from scripture is one of the ways that Christians test their moral judgments. But are all methods of appealing to the Bible equally valid and effective? In this book, Charles Cosgrove looks at the church's long tradition of moral debate and uncovers five central rules that can best guide the use of scripture in contemporary ethical debates. After introducing the nature of moral arguments generally, Cosgrove devotes one chapter to each of the five rules of biblical interpretation that make ethical appeals to scripture persuasive. He sets forth each rule's rationale, provides examples of its operation, and subjects it to critique. Based not only on the work of biblical scholars and Christian ethicists but also on Cosgrove's own experience with debates in classrooms, churches, and other Christian contexts, this volume is a valuable aid to readers who employ moral reasoning in real-life settings. - Publisher
The rule of purpose -- The rule of analogy -- The rule of countercultural witness -- The rule of nonscientific scope -- The rule of moral-theological adjudication
Includes bibliographical references (pages 202-215) and indexes
Keywords: Ethics in the Bible